A prospective observational study: combined irrigation of bupivacaine at the gallbladder fossa with infiltration at port site for postoperative pain relief after laparoscopic cholecystectomy - Paliwal, Palak; Huda, Tanweerul; Anand, Krishnanand; Shivani, Manish; Mishra, Navneet (International Surgery Journal, 2020)
Background: Laparoscopic cholecystectomy is a well-established procedure for gallbladder disease. Pain in laparoscopic cholecystectomy is associated with multiple factors: somatic, visceral, and phrenic nerve irritation. Effective analgesic support should, therefore, be a multimodal approach following laparoscopic surgery for better patient compliance. Methods: A prospective, randomized observational study was undertaken at a tertiary research center for a period of two years (2018-2020). 160 patients undergoing laparoscopic cholecystectomy were chosen and randomized using a computer program into 2 groups. No infiltration was given in the control population. The study group was irrigated with a 0.5% bupivacaine solution (20cc in 30 ml normal saline). Results: The bupivacaine group required fewer analgesics in comparison to the control faction, with less pain at 6 hrs. The timing of oral intake and ambulation were comparable in both factions. Conclusions: Combined bupivacaine use led to a considerable decrease in postoperative pain thereby leading to decreased analgesic use.